Perubahan Luas Dan Kerapatan Mangrove Di Kawasan Pesisir Kota Serang, Banten - Rahayu, Risma Warni; Yudha, Indra Gumay; Yuliana, Darma; Damai, Abdullah Aman (Journal of Tropical Marine Science, 2025)
Changes in the area and density of mangroves have a major impact on the sustainability of ecosystem functions in coastal areas. This study aims to analyze changes in the area and density of mangroves in Serang City, Banten. The method used is remote sensing through interpretation of Landsat 5 and Landsat 8 images with analysis of changes in the area and density of mangroves in 2011 and 2021. The research procedure was carried out by grouping NDVI values ​​into 3 vegetation classes: sparse, moderate, and dense. Furthermore, a ground check was carried out to test the level of data accuracy against mangrove canopy cover using the hemispherical photography method. The results showed that the level of image accuracy in 2021 was 90%. Based on this analysis, it is known that there has been a decrease in the area and changes in mangrove density in Sawah Luhur Village, while in Banten Village it has increased. In general, in the coastal area of ​​Serang City, there was a decrease in the mangrove area between 2011-2021 which reached 13.95 ha with the main decrease occurring in mangroves with sparse vegetation class (33.14 ha). In contrast, mangroves with medium and dense density categories increased to 19.19 ha. The decrease in mangrove area was due to abrasion, conversion into ponds, and illegal logging. The results of the analysis also showed that the correlation between NDVI values ​​and the percentage of canopy cover had a value of 0.696 which was included in the strong category.